2001
DOI: 10.1097/00001813-200111000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor effect of gallic acid on LL-2 lung cancer cells transplanted in mice

Abstract: We previously reported that gallic acid (3,4,5-trihydroxybenzoic acid), a naturally occurring plant phenol, can induce apoptosis in four kinds of human lung cancer cell lines in vitro. The present study further investigated the in vivo anti-tumor effects of orally administered gallic acid. Gallic acid reduced cell viability of LL-2 mouse lung cancer cells in vitro dose dependently, with a 50% inhibitory concentration (IC50) value of around 200 microM. C57Black mice were transplanted with LL-2 cells, and admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(75 citation statements)
references
References 20 publications
1
69
0
1
Order By: Relevance
“…its various biological activities, such as anti-bacterial (3), anti-viral (4) and anti-inflammatory (5), have been reported, and the anti-cancer activity of Ga has been reported in various types of cancer cells, such as prostate (6), lung (7,8), gastric, colon, breast, cervical and esophageal (9). cell death induced by Ga is associated with oxidative stress derived from reactive oxygen species (roS), mitochondrial dysfunction and an increase in intracellular ca 2+ level (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…its various biological activities, such as anti-bacterial (3), anti-viral (4) and anti-inflammatory (5), have been reported, and the anti-cancer activity of Ga has been reported in various types of cancer cells, such as prostate (6), lung (7,8), gastric, colon, breast, cervical and esophageal (9). cell death induced by Ga is associated with oxidative stress derived from reactive oxygen species (roS), mitochondrial dysfunction and an increase in intracellular ca 2+ level (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The cells were treated with 200 and 250 μM GA for 0, 12, 24, 48 and 72 h. Cells (1x10 5 cells per sample) were centrifuged at 1000 x g for 5 min, cell pellets were dissolved with 0.5 ml of PBS containing 5 μg/ml PI and viable cells were deter-mined by using FACSCalibur utilizing CellQuest software (Becton-Dickinson, San Jose, CA, USA) for determination of viable cells as previously described (14)(15)(16).…”
Section: Assessment Of Cell Viabilitymentioning
confidence: 99%
“…It was also reported that GA plays an important role in the prevention of malignant transformation (13) and GA prevents amyloid ß-induced apoptotic neuronal death by interfering with the increase of Ca 2+ levels and then by inhibiting glutamate release and generation of ROS (14). GA was shown to have antitumor effects on LL-2 lung cancer cells transplanted in mice (15) and NCI-H460 human lung cancer cells in vitro and in vivo (10). However, there is no study to show that GA affected A375.S2 human melanoma cells.…”
Section: Introductionmentioning
confidence: 98%
“…Various biological effects of Ga have been reported, including anti-bacterial (3), anti-viral (4) and anti-inflammatory activities (5). The major point of interest in Ga is related to its anti-cancer activity, which has been reported in various cancer cells, including prostate (6), lung (7,8), gastric, colon, breast, cervical and esophageal cancer (9). apoptosis induced by Ga is associated with oxidative stress derived from reactive oxygen species (roS), mitochondrial dysfunction and an increase in intracellular ca 2+ levels (10,11).…”
Section: Introductionmentioning
confidence: 99%